Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1128/jb.179.2.317-322.1997
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of horizontal gene transfer and deletion events to development of distinctive patterns of fimbrial operons during evolution of Salmonella serotypes

Abstract: Only certain serotypes of Salmonella represent 99% of all human clinical isolates. We determined whether the phylogenetic distribution of fimbrial operons would account for the host adaptations observed for Salmonella serotypes. We found that three fimbrial operons, fim, lpf, and agf, were present in a lineage ancestral to Salmonella. While the fim and agf fimbrial operons were highly conserved among all Salmonella serotypes, sequence analysis suggested that the lpf operon was lost from many distantly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
90
0
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 53 publications
3
90
0
10
Order By: Relevance
“…Studies concerning the frequency of these genes are important in tracking the adaptation of different serovars of Salmonella spp. to an increasing number of hosts because the acquisition and loss of fimbrial genes are involved in this process (Bäumler et al 1997). The high frequency of sefA is consistent with previous findings (Amini et al 2010, Craciunas et al 2012, and it can be considered a target gene to identify the serovar S. Enteritidis by PCR (Amini et al 2010).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Studies concerning the frequency of these genes are important in tracking the adaptation of different serovars of Salmonella spp. to an increasing number of hosts because the acquisition and loss of fimbrial genes are involved in this process (Bäumler et al 1997). The high frequency of sefA is consistent with previous findings (Amini et al 2010, Craciunas et al 2012, and it can be considered a target gene to identify the serovar S. Enteritidis by PCR (Amini et al 2010).…”
Section: Discussionsupporting
confidence: 79%
“…The highest frequency of P1 profile demonstrate that these genes are widely distributed in the population of Salmonella spp. The presence of more than one genetic profile may suggest acquisitions or deletions of genes in different clones, which could promote different levels of strain adaptation to the host (Bäumler et al 1997, Prager et al 2000, Moussa et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For pathogenic Salmonella spp., genome sequencing efforts have identified over 15 distinct fimbrial types (Salmonella enterica serovars Typhimurium [42], Typhi [44], and Paratyphi [41]). Pioneering work by Baumler et al (5) and subsequent genomic comparisons (14,45,61) revealed that most fimbrial operons have a scattered distribution throughout the salmonellae. Early hypotheses that fimbriae were involved in adherence to host cells suggested that numerous fimbrial types would contribute to the host specificities and tissue tropisms of different Salmonella spp.…”
mentioning
confidence: 99%
“…The divergent agfDEFG/BAC (csgDEFG/BAC) operons coding for Tafi biosynthesis have been detected in almost all Salmonella isolates tested to date (5,18). Virtually identical operons have also been identified in Escherichia coli and other enterobacterial species (8,49,69).…”
mentioning
confidence: 99%